A method for detecting continuous gravitational wave signals from an ensemble of known pulsars. (4th June 2021) - Buono, M; De Rosa, R; D'Onofrio, L; Errico, L; Palomba, C; Piccinni, O J; Sequino, V
Abstract: This work describes a method to improve the detection efficiency for continuous gravitational waves by combining information from known pulsars, which emission is too low to be individually detectable. We propose a new ensemble statistic t, which combines statistics from individual pulsars, defined through the five-vector method. Using a collection of band sample data files from the LIGO science run O2, we test the method with software injections in order to study the statistical properties of t . We also study the performance of our method by varying the number of injected signals and their amplitude. We propose and test a possible strategy for the application of the ensemble method to a set of real pulsars.